Effects of Dynamic Vulcanization and Glycidyl Methacrylate (GMA) on mechanical properties, swelling index and morphology properties of Recycled Poly(vinyl chloride)/Acrylonitrile Butadiene Rubber (PVCr/NBR) blends - Supri; Hanafi, Ismail (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my